Excelsior: Earth observation opportunities for excellence in the Emmena Region - Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Michaelides, Silas; Neocleous, Kyriacos; Schreier, Gunter; Ansmann, Albert; Kontoes, Haris; Komodromos, George (My University, 2020)
The ERATOSTHENES Centre of Excellence for Earth Surveillance and Space-Based Monitoring of the Environment (ECoE) that will be established through the EXCELSIOR project will provide cutting-edge Earth Observation (EO) research in Cyprus, the Eastern Mediterranean, Middle East and North Africa (EMMENA) region, Europe and Internationally for the benefit of the environment and society. The ECoE will focus on the thematic clusters of Environment and Climate, Resilient Society and Big Earth Data Analytics and conduct research and develop applications within the focus areas of climate change monitoring, disaster risk reduction, access to energy, water resources management and big EO data analytics. The ECoE can serve as an innovation gateway for Cyprus and EMMENA in the areas of Earth observation and remote sensing, thereby providing applications and services for issues that are unique to the EMMENA region. The success indicators to measure the ECoE’s sustainability are also discussed.
Keywords: EXCELSIOR; Centre of Excellence; Cyprus; EMMENA; Earth Observation; Remote Sensing